Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

O papel da educação para a igualdade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 2005-2015 - Lucas, Geraldo Cebola João (Revista Litteris, 2015)
Este artigo tem como objecto “o contributo da educação para a equidade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 1997-2015”. O terceiro objectivo do milénio defende que para que possa alcançar o desenvolvimento sustentável nos países em vias de desenvolvimento e mesmo os já industrializados é preciso que a questão de género seja tomada como primordial nas políticas e estratégias de desenvolvimento. E tal pressuposto requer, como se defende nos objectivos, uma equidade de género e seu paralelo empoderamento. Porque acredita-se que a questão de género é transversal. É preocupação nesta pesquisa verificar se as políticas de género em Moçambique estão em consonância com o terceiro objectivo do milénio. Em segundo lugar, verificar o grau do cumprimento do terceiro objectivo do Milénio na cidade de Lichinga. A pesquisa é norteada pela seguinte pergunta de pesquisa: “ em que medida as políticas da educação moçambicana têm contribuído para a equidade e empoderamento do género no quadro do terceiro objectivo do milénio?”.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - portuguese / português; education / educação; empowerment / empoderamento; gender / género; youth / juventude

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza